(Re)-fashioning the Techno-erotic Woman: Gender and Textuality in the Cybercultural - Handayani, Diah (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2021)
This study examines the techno-journals and futuristic zines such as Boing Boing inscribe a kind of textual prologue for cyber-culture. They are valuable in themselves because they forge a much-needed connection between late print culture and the new cyberspatial network, formatting the matrix of this social space in ways that begin to define it. Wired magazine, for instance, participates in a cultural dialogue concerning issues of network privacy, governmental regulation, and censorship. Wired also sponsors HotWired, its online counterpart, where participants can exchange information, chat with live guests, and buy, sell, or trade computers and software products. Boing Boing, while differing from Wired in their hyperbolic presentation, share the techno-journal's fascination with